Pengaruh Viral Marketing, Online Marketing, Dan Lifestyle Terhadap Buying Decision (Studi Kasus pada Mahasiswa FEB UNISMA Angkatan 2017 yang Membeli Sepatu Converse) - Faisol Faisol; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of viral marketing, online marketing, and lifestyle on buying decisions. The independent variables in this study are viral marketing, online marketing, and lifestyle. While the dependent variable is the buying decision. This type of research is quantitative research, because the primary data with data collection methods is in the form of a questionnaire via google form. The population in this study were customers from FEB UNISMA students batch 2017 who had bought Converse shoes. The data collection technique was carried out using Lemeshow's theoretical technique. Based on this method the number of samples used is 96 respondents. The hypothesis was tested using descriptive statistical analysis, instrument testing, normality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that viral marketing variables affect buying decisions, online marketing variables affect buying decisions, and lifestyle influences buying decisions. Keywords: Viral Marketing, Online Marketing, Lifestyle, Buying Decision